Three-dimensional numerical analysis on seismic behavior of soil-piled raft-structure system. (December 2020) - Chaudhuri, Chaidul Haque; Chanda, Diptesh; Saha, Rajib; Haldar, Sumanta
Abstract: Increasing demand for high-rise buildings and other important structures in urban areas and unfavorable land has resulted to opt for piled raft foundation by the designers. The present study is an attempt to investigate the seismic behavior of piled raft foundation supporting structural system embedded in very soft clay encompassing variations of different influential parameters. The piled raft system is modeled using three-dimensional (3D) finite element analysis. At first, the 3D numerical model is validated with past numerical studies. This is followed by a detailed parametric study on the effect of different influential parameters, such as flexibility of raft, pile spacing to diameter ratios, and asymmetry in pile length on dynamic characteristics and seismic response of the piled raft foundation system considering dynamic soil-structure interaction (DSSI). It is observed that the fundamental period of the structure gets significantly lengthened with increasing raft flexibility whereas pile head shear considerably reduced. Further, non-identical pile lengths attributing asymmetric group configuration results in a significant change in the fundamental period of the structure and pile head shear.